Prevalence of alcohol related attendance at an inner city emergency department and its impact: a dual prospective and retrospective cohort study. Issue 3 (23rd December 2015) - Parkinson, Kathryn; Newbury-Birch, Dorothy; Phillipson, Angela; Hindmarch, Paul; Kaner, Eileen; Stamp, Elaine; Vale, Luke; Wright, John; Connolly, Jim
Abstract : Background: Alcohol related hospital attendances are a potentially avoidable burden on emergency departments (EDs). Understanding the number and type of patients attending EDs with alcohol intoxication is important in estimating the workload and cost implications. We used best practice from previous studies to establish the prevalence of adult alcohol related ED attendances and estimate the costs of clinical management and subsequent health service use. Methods: The setting was a large inner city ED in northeast England, UK. Data were collected via (i) retrospective review of hospital records for all ED attendances for four pre-specified weeks in 2010/2011 to identify alcohol related cases along with 12 months of follow-up of the care episode and (ii) prospective 24/7 assessment via breath alcohol concentration testing of patients presenting to the ED in the corresponding weeks in 2012/2013. Results: The prevalence rates of alcohol related attendances were 12% and 15% for the retrospective and prospective cohorts, respectively. Prospectively, the rates ranged widely from 4% to 60% across week days, rising to over 70% at weekends. Younger males attending in the early morning hours at weekends made up the largest proportion of alcohol related attendances. The mean cost per attendance was £249 (SD £1064); the mean total cost for those admitted was £851 (SD £2549). The most common reasons for attending were trauma related injuries followed by psychiatric problems. Conclusions: Alcohol related attendances are a major and avoidable burden on emergency care. However, targeted interventions at weekends and early morning hours could capture the majority of cases and help prevent future re-attendance.